A hybrid LSQP algorithm for simultaneous reconstruction of the temperature and absorption coefficient field from the light-field image - Wen, Shuang; Qi, Hong; Liu, Shao-Bin; Ren, Ya-Tao; Shi, Jing-Wen; Huang, Xing (Infrared physics & technology, 2020)
•The temperature field and absorption coefficient can be retrieved simultaneously.•Estimated accuracy of absorption coefficient is lower than that of temperature.•Reconstructed distribution of temperature is accordance with the map of flame.•Estimated results of absorption coefficient is accordance with the map of flame. A hybrid Landweber method and the sequential quadratic programming (LSQP) algorithm is developed to reconstruct the three dimensional temperature field and absorption coefficient of flame by the light-field imaging technique. The line-of-sight method is employed to solve the direct problem of the radiative transfer procedure in flame. Numerical experiments are performed to verify the hybrid inverse algorithm and effect of measurement errors on the computational accuracy is also studied. All the simulated results show that the hybrid LSQP algorithm performs reliably and robustly. Furthermore, an experimental measurement is developed to reconstruct the temperature and absorption coefficient of the ethylene diffusion flame from the light-field image. All the experimental results show the proposed LSQP method is capable of reconstructing the 3D distribution of temperature and absorption coefficient simultaneously.